DESCRIPTION OF LEARNING RESOURCES WHICH ARE WIDELY USED IN PRIMARY SCHOOLS - Urik Taurik; Moh Abdurahman K maruf (Jurnal Ilmu Pendidikan dan Budaya, 2024)
This research aims to re-analyze the use of learning media in improving elementary school learning outcomes. The method used in this research is. This research began by looking for relevant topics to make it easier for the writer to collect data. This data was obtained by searching online journals via Google Academia with the keyword Learning Media. Learning media in elementary school not only functions as a means of conveying information, but also as a tool to stimulate student interest and involvement in the learning process. The use of this media involves not only traditional aspects such as textbooks, but also utilizing the latest technology. The diversity of media, such as images, audio, video and software interactivity, ensures that learning is not only informative, but also entertaining and motivating for students. Therefore, learning media in elementary school is not just a tool, but also a catalyst for developing students' critical skills and creativity. The research results show that the integration of various learning media can increase learning effectiveness by providing a learning experience that is more interesting and responsive to students' learning styles.